Republic of San Marino : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This 2014 Article IV Consultation on the Republic of San Marino highlights global crisis and tense relations with Italy, which triggered a 30 percent GDP contraction since 2008 and a sea change in San Marino's off-shore banking model. High liquidity in the system allowed banks to withstand the shock to deposits. Cassa di Risparmio della Repubblica di San Marino, the largest bank, has required 13 percent of GDP in public support. The deep recession and bank recapitalization costs are weighing heavily on public finances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet